Positively no Filipinos allowed building communities and discourse - Tiongson, Antonio T. 1968-; Gutierrez, Edgardo V. (Edgardo Valencia) 1969-; Gutierrez, Ricardo V. (Ricardo Valencia) 1971- (Asian American history and culture, 2008)
"Taken together, the essays in Positively No Filipinos Allowed vigorously pursue Filipino American critique. They insist that the forgetting that renders the Filipino American 'lost to history' must be made visible and intelligible."--Foreword by Lisa Lowe.